(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Education and socialization are fundamental processes that shape individuals’ integration into society. This paper explores the roles of schools and media in this socialization process, highlighting their distinct contributions and interactions. Schools provide formal education and impart societal values through both explicit curricula and implicit lessons, known as the hidden curriculum. They also influence social stratification by reinforcing existing social hierarchies. Media, on the other hand, acts as a powerful cultural agent, shaping individuals’ perceptions of identity and societal norms through various platforms such as television, the internet, and social media. The interaction between schools and media can both complement and conflict, affecting how individuals internalize social expectations and values. By examining these institutions’ roles and their impact on socialization, this paper provides insights into how contemporary socialization processes are constructed and maintained.